1H and 13C NMR Spectra of Natural Products Laurene-Type Sesquiterpenes: Theoretical and Experimental Studies - Mohamed Alarif, Walied; Hassan Abdel-Rhman, Mohamed; Abdel-Lateff, Ahmed; Samran Al-Lihaibi, Sultan (Asian Journal of Chemistry, 2014)
Quantum chemical calculations for geometrical optimization of the natural products laurene-type sesquiterpenes, 12-hydroxy isolaurene (1), 8,11-dihydro-12-hydroxy isolaurene (2) and isolauraldehyde (3) isolated from the red alga Laurencia obtusa using density functional theory (DFT) were carried out. A comparable study between experimental 1H and 13C NMR spectral data and calculated with DFT and ab initio Hartree-Fock (HF) methods were used to confirm the spectral data assignments of compounds 1-3. The calculated NMR spectral data showed good agreement with the experimental data supporting the obtained geometries. Among the studied methods, DFT/B3LYP method is most convenient one for prediction of 1H and 13C NMR spectra of such compounds.